Implementasi Media Smart Pop-up Book untuk Edukasi Kesehatan Seksual dan Reproduksi Anak Berkebutuhan Khusus di TK-SD Inklusi Fun & Play Semarang - Dian Nintyasari Mustika; Sugiyani; Carlin Souhaly; Sarah Semaher Nurrihan; Salma Septiana Nurfadilla; Khoirotun Nahda (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2026)
Violence and sexual abuse against children remain a public health issue, particularly for children with disabilities, who are more vulnerable than the general population. Early sexual and reproductive health education is a crucial preventive measure, yet its implementation in inclusive schools still faces obstacles. Based on a problem identification process involving 7 teachers at the Fun & Play  Inclusive Kindergarten and Primary School in Semarang, several challenges faced by the partners were identified, including limited resources, difficulties in delivering sensitive material, and the diversity of pupils’ characteristics. This community service activity aims to evaluate the acceptability, appropriateness, and feasibility of implementation of the Smart pop-up book as an educational tool for sexual and reproductive health among children in inclusive nursery and primary schools. This community service activity was conducted using a Focus Group Discussion (FGD) approach and outreach activities carried out through four stages: problem identification, solution design, programme implementation, and evaluation. Problem identification was carried out through FGDs to assess the needs and barriers experienced by teachers. Programme evaluation was conducted using the Acceptability of Intervention Measure (AIM), Intervention Appropriateness Measure (IAM), and Feasibility of Intervention Measure (FIM) questionnaires, which were subsequently analysed descriptively. The evaluation results showed an average acceptability score of 99.3%, an appropriateness score of 91.4%, and a feasibility score of 90%. These findings indicate that the Smart pop-up book was very well received, aligned with the needs of teachers and pupils, and was easy to implement in inclusive school settings.  Consequently, this resource has the potential to support the prevention of sexual violence against children with disabilities through an engaging, concrete, and adaptive.   ABSTRAK Kekerasan dan pelecehan seksual pada anak masih menjadi masalah dalam aspek kesehatan masyarakat, terutama pada anak dengan disabilitas yang memiliki kerentanan lebih tinggi dibandingkan dengan populasi umum. Edukasi kesehatan seksual dan reproduksi sejak dini menjadi sebuah upaya preventif yang sangat penting, namun implementasinya di sekolah inklusi masih menghadapi hambatan. Berdasarkan identifikasi masalah dengan 7 guru di TK-SD Inklusi Fun & Play Semarang, diperoleh beberapa permasalahan yang dihadapi mitra, meliputi keterbatasan media, kesulitan penyampaian materi yang sensitif, serta keberagaman karakteristik siswa. Kegiatan pengabdian masyarakat ini bertujuan mengevaluasi penerimaan, kesesuaian, dan kemudahan penerapan media Smart pop-up book sebagai saran edukasi kesehatan seksual dan reproduksi pada anak TK-SD inklusi. Kegiatan pengabdian masyarakat ini dilakukan melalui pendekatan Focus Group Discussion (FGD) dan sosialisasi yang dilaksanakan melalui empat tahapan, yaitu identifikasi masalah, perancangan solusi, pelaksanaan program, dan evaluasi. Identifikasi masalah dilakukan melalui FGD untuk mengkaji kebutuhan dan hambatan yang dialami guru. Evaluasi program dilakukan menggunakan kuesioner Acceptability of Intervention Measure (AIM), Intervention Appropriateness Measure (IAM), dan Feasibility of Intervention Measure (FIM), kemudian dianalisis secara deskriptif. Hasil evaluasi menunjukkan rerata skor acceptability  sebesar 99,3%, appropriateness sebesar 91,4%, dan feasibility sebesar 90%. Temuan ini menunjukkan bahwa media Smart pop-up book diterima dengan sangat baik, sesuai dengan kebutuhan guru dan siswa, serta mudah diterapkan dalam pembelajaran di sekolah inklusi. Dengan demikian, media ini berpotensi menjadi inovasi edukatif dalam mendukung pencegahan kekerasan seksual pada anak dengan disabilitas melalui pendekatan pembelajaran yang menarik, konkret dan adaptif.